NEGOTIATIONS AND MEDIATION: FROM DIFFERENTIATION TO MUTUAL COMPLEMENTARITY - Bartusiak Pavlo (Legal Bulletin, 2021)
Due to the permanent crisis in the judicial system Ukraine is constantly reforming the organization of courts, improving the legal regulation of the administration of justice. On the other hand, from the society itself, like mushrooms after the rain, there emerge alternative ways of resolving disputes, including negotiations and mediation. The purpose of this article is to study the variants for understanding by the scientific community of such concepts as «negotiation» and «mediation» through the use of methods of comparison, analysis and synthesis. The article demonstrates the existence of several approaches to the definition of negotiation and mediation, which are characterized by the differentiation of these phenomena or their complementarity by each other. The models for understanding of negotiation and mediation, that proposed in the article, will help all those, who are interested in these ways of alternative disputes resolution, to better understand their essence and purpose, to successfully apply negotiation techniques during mediation sessions.